CONJOINT ANALYSIS OF SHRIMP ATTRIBUTES FOR EXPORTS FROM ANDHRA PRADESH - K. J. V. K SIRISHA; D. V. SUBBA RAO (The Journal of Research ANGRAU, 2024)
The shrimps export demand was influenced by various attributes. To determine which characteristics have contributed most to shrimp exports over time, a conjoint analysis is employed. This method is mostly used in marketing research to determining the relative significance of each attribute for a commodity/service. This study identified the important attributes to develop the successful marketing strategies for shrimp exports.The survey was conducted during August-September 2022.The results indicated that all the eight attributes viz: physical form, odour, colour, size, nature of shrimp, certification and labeling, price and branding were significant in nature. The individual utilities of physical form of the shrimp viz., raw frozen, cooked/ value added (breaded, prawn pickle, etc.) and live shrimp was 0.815, 0.472 and 0.343, respectively. Shrimp exporters are preferred to export raw frozen shrimps with minimal processing. Certification and labelling attribute are categorized into three sub attribute levels i.e. high standards, medium standards and low standards, the utilities for these are 0.722, 0.547 and -1.263. Whereas, sensory attributes like colour and odour were bright pink colour with strong marine odour had highly preferred attribute levels with utility values 1.471 and 0.97.